Assessing the role of internal phosphorus recycling on eutrophication in four lakes in China and Malaysia - Tay, Chai Jian; Koh, Hock Lye; Mohd Hafiz, Mohd; Teh, Su Yean (Elsevier B.V., 2022)
Internal phosphorus recycling (IPR) is an important nutrient source driving algal growth and eutrophication in lakes. The complexity of eutrophication behaviours caused by high IPR complicates lake management and undermines restoration efforts. Hence, knowledge about the possible types of bifurcation behaviours caused by high IPR is essential for effective and sustainable lake eutrophication management. For this purpose, numerical bifurcation analysis is performed on an algae phosphorus model to investigate how IPR drives complex and rich eutrophication behaviours in two tropical and two subtropical lakes. The two tropical lakes are Tasik Harapan and Sunway Lagoon in Malaysia, while the two subtropical lakes are Lake Fuxian and Lake Taihu in China. For each specified level of IPR, co-dimension one bifurcation analysis is performed by means of XPPAUT. Co-dimension two bifurcation analysis is then carried out by means of MatCont. At low IPR, Lake Fuxian exhibits reversible behaviour, accompanied by higher external phosphorus loading (EPL) thresholds. Lake Fuxian is also more conducive to stable equilibrium and its lake dynamics are easily predictable. At moderate IPR, Sunway Lagoon is likely to exhibit stable equilibrium, accompanied by possible shifting between two stable steady states (hysteresis behaviour) and oscillations. With higher IPR, Lake Taihu and Tasik Harapan are prone to irreversibility, accompanied by lower EPL thresholds. Because of increased complexity in lake dynamics in Lake Taihu and Tasik Harapan, small changes in EPL or in algal mortality rates could trigger various transitions in lake dynamics. Overall, high IPR can trigger unexpected sharp increases in algal concentration and can reduce the resilience of an oligotrophic lake. For shallow lakes, high IPR would cause unexpected sharp increases in algal concentrations, undermine resilience of lakes, complicate lake management, and delay lake recovery process.